THEORETICAL ASPECTS OF MARKETING RESEARCH WHEN PERFORMING FOREIGN ECONOMIC ACTIVITY BY THE ENTERPRISE - KOVTUN, E. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The effectiveness of production and economic activities of enterprises engaged in foreign economic activity and focused on long-term presence in foreign markets, largely depends on the right strategic goals and scientifically sound ways to implement them based on the analysis of the market environment. Solving these problems requires thorough marketing research on the state and features of foreign markets, the correct use of specific approaches and tools of marketing activities to develop and implement the most optimal ways for companies to enter foreign markets and ensure effective foreign economic activity by enterprises.Among the reasons for the protracted crisis of the Ukrainian economy are inefficiency, inconsistency of traditional technologies, tools and methods of interaction of enterprises with consumers. All this leads to a reduction in the life cycle of goods and the advantage of non-price factors over price, based on the position of meeting consumer requirements, the development of digital technologies, the need to personalize production and consumption.In the current conditions of domestic economic transformations, Ukrainian industry is integrated into world trade rules through the introduction of international quality standards for management and production and economic activities. At the same time, the dynamics of sales of industrial enterprises (including foreign markets), Ukraine's positioning in international competitiveness rankings indicate not fully realized the potential for the operation and development of industrial enterprises for sales in foreign markets. In turn, this requires the development of a methodology for the formation of such a mechanism in the process of marketing research, which would be focused on balancing the internal capabilities and external needs of enterprises by ensuring continuous and multi-channel contact with consumers. That is why the intensification of comprehensive research in the direction of developing methods of marketing research of markets in the implementation of foreign economic activity by enterprises is relevant.The article is devoted to the issue of marketing research in the implementation of foreign economic activity, as the objective need for constant study of marketing research by the company involves scientific and methodological processing of the analysis of competition in domestic and foreign markets to increase the likelihood of market success.
Keywords: marketing; management efficiency; external environment; foreign economic activity; competition; foreign marke